2014
DOI: 10.1093/hmg/ddu350
|View full text |Cite
|
Sign up to set email alerts
|

SMN regulates axonal local translation via miR-183/mTOR pathway

Abstract: Reduced expression of SMN protein causes spinal muscular atrophy (SMA), a neurodegenerative disorder leading to motor neuron dysfunction and loss. However, the molecular mechanisms by which SMN regulates neuronal dysfunction are not fully understood. Here, we report that reduced SMN protein level alters miRNA expression and distribution in neurons. In particular, miR-183 levels are increased in neurites of SMN-deficient neurons. We demonstrate that miR-183 regulates translation of mTor via direct binding to it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
118
1
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 132 publications
(133 citation statements)
references
References 57 publications
10
118
1
1
Order By: Relevance
“…Notably, in stimulated SMN-knockdown cells, phospho-S6 immunostaining appeared diffuse throughout the cytoplasm, without peripheral accumulations. Apparently, our findings are in disagreement with the notion that SMN deficiency dysregulates mTOR activity (Kye et al, 2014). However, we do not exclude perturbed translational events downstream of mTOR.…”
Section: Smn Loss Of Function Depletes the Plasma Membrane Of Ribosomescontrasting
confidence: 99%
See 1 more Smart Citation
“…Notably, in stimulated SMN-knockdown cells, phospho-S6 immunostaining appeared diffuse throughout the cytoplasm, without peripheral accumulations. Apparently, our findings are in disagreement with the notion that SMN deficiency dysregulates mTOR activity (Kye et al, 2014). However, we do not exclude perturbed translational events downstream of mTOR.…”
Section: Smn Loss Of Function Depletes the Plasma Membrane Of Ribosomescontrasting
confidence: 99%
“…It has been reported that dysregulated mTOR signalling occurs in the SMA disease context (Kye et al, 2014). This prompted us to verify whether, in our SMN-depleted cells, the perturbation of actin network combines with a reduced mTOR activity.…”
Section: Smn Loss Of Function Depletes the Plasma Membrane Of Ribosomesmentioning
confidence: 81%
“…Similarly, reduced levels of survival of motor neuron (SMN) decrease axonal mRNA localization and human SMN1 mutations that alter the amount of functional protein are responsible for most SMA cases [42]. Reduced SMN levels, such as seen in SMA, cause increase expression of microRNA-138, which, in turn, leads to reduced local mammalian target of rapamycin synthesis and activity in axons [43]. For both these examples it has been suggested that impaired local translation of localized mRNAs at the neuromuscular junction contributes to the pathogenesis of ALS, SMA, and related disorders [44]; however, direct proof from in vivo studies is sparse.…”
Section: Neurodegenerative Disordersmentioning
confidence: 99%
“…The mRNA expressions were calculated in accordance with a previous protocol [28]. Briefly, total RNA was reversely transcribed to cDNAs [Archiving Kit (Life Tech, USA)], which were then amplified [Power SyBr Green PCR Master Mix (Life Tech, USA)].…”
Section: Determination Of Expressions Of Mir-183 Mtor and Vegfmentioning
confidence: 99%